2019
DOI: 10.1016/bs.ampbs.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Roles and regulation of Spx family transcription factors in Bacillus subtilis and related species

Abstract: Bacillus subtilis Spx is the prototype for a large family of redox-responsive transcription factors found in many bacteria, most notably those from the phylum Firmicutes. Unusually for a transcription factor, B. subtilis Spx protein modulates gene expression by binding as a monomer to the αCTD domain of RNA polymerase (RNAP), and only interacts with DNA during subsequent promoter engagement. B. subtilis Spx drives the expression of a large regulon in response to proteotoxic conditions, such as heat and disulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…Spx, initially named as s uppressor of clp P and clp X , is highly conserved among low GC-content Gram-positive bacteria and is widely distributed in the phylum Firmicutes, including some disseminated human pathogens ( 23 , 24 ). Genetic and biochemical studies have shown that B. subtilis Spx is a pleiotropic transcriptional regulator that responds to various stresses (such as oxidative stress, thermo damage, and cell wall-active antibiotics) and serves as a prototype for a large group of stress-response regulators ( 25–29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spx, initially named as s uppressor of clp P and clp X , is highly conserved among low GC-content Gram-positive bacteria and is widely distributed in the phylum Firmicutes, including some disseminated human pathogens ( 23 , 24 ). Genetic and biochemical studies have shown that B. subtilis Spx is a pleiotropic transcriptional regulator that responds to various stresses (such as oxidative stress, thermo damage, and cell wall-active antibiotics) and serves as a prototype for a large group of stress-response regulators ( 25–29 ).…”
Section: Introductionmentioning
confidence: 99%
“…The strongest downregulation is that of Spx transcription factor and, while not unique to 8-1, it is more than five times stronger in this strain than in Ym1 (20.62- vs. 3.8-fold). The Spx transcription factors usually interact directly with the RNA polymerase and are mostly involved in oxidative stress; several species of LAB have been reported to contain from two to seven Spx paralogs [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Proteins in bold were further studied. Identified Proteins cellular process BrxB [ 3 ] bacilliredoxin BdhA [ 3 ] acetoine/butanediol dehydrogenase SalA [ 1 ] control of alkaline protease expression PyrH [ 1 ] pyrimidine biosynthesis PyrAA [ 6 ] pyrimidine biosynthesis PyrAB [ 8 ] pyrimidine biosynthesis PyrG [ 7 ] pyrimidine biosynthesis PyrE [ 4 ] pyrimidine biosynthesis GapB [ 4 ] glycolysis PfkA [ 3 ] glycolysis YtsJ [ 3 ] NADP-dependent malate dehydrogenase SucC [ 4 ] tricarboxylic acid cycle Bdr (YpdA) [ 3 ] oxidoreductase activity FolD [ 3 ] formylation of Met-tRNA(fMet) AbrB [ 1 ] transition state regulator TufA [ 2 ] elongation factor Tu (translation) RpsB [ 1 ] translation GatA [ 3 ] ...…”
Section: Resultsmentioning
confidence: 99%
“…Cells contain several systems to maintain cysteine residues and other thiols in their reduced form in the cytosol, and dedicated pathways for the controlled oxidation of cysteines to form disulfide bonds in secreted and periplasmic proteins. Maintaining the redox balance of cellular thiols is critical for cell physiology, and oxidation can lead to a specific type of oxidative stress known as disulfide stress [ [1] , [2] , [3] , [4] ]. Reduction of intracellular thiols ultimately relies on the reducing power of NADPH, which serves as a cofactor to reduce thiol groups in either protein-based thiol reductants like thioredoxin (Trx) or low molecular weight (LMW) thiols.…”
Section: Introductionmentioning
confidence: 99%